Business process re-engineering to support cake shop business sustainability - Anam, Khoirul; Hidayat, Kharis Rahmat; Nugroho, Alifio Ibnu; Hutahaean, Kevin Tito (SHM Publisher, 2022)
Business Process Re-engineering is usually carried out to increase satisfaction with goods or services so that customers tend to choose goods or services from certain companies rather than choosing goods or services from competing companies. This cake shop has been around since 2000, but previously in 1999 they had tried to process the cake shop's recipe so that they found a concoction that suited the local people's tongue. However, this business did not last long because the shop they owned had experienced a fire incident which caused the cake shop business to be evicted and eventually moved to another place so that they also received business threats, namely the emergence of many competitors selling similar products. The purpose of our research is that we will conduct a re-engineering analysis to optimize the business processes in the cake shop. The research method used in our research is descriptive. The descriptive research method is carried out by seeking information related to existing symptoms, clearly explaining what goals will be achieved in the research conducted. In this new model, we add a promotion method, namely by using advertising services on social media so that it can reach people who are still not familiar with the product. In the new model, we also added a process, namely a research process to add innovation to new product cake variants that will give a new impression to the shop's customers.